Strategi Bertahan Hidup Kelompok Tani Tebu Sri Dadi SebagaiDampak Pembatasan Distribusi Pupuk Subsidi (Studi Kasus Di Desa Gondang, Kecamatan Karangrejo) - Vina Nurita Rohmawati; Dwi Astutik; Danang Purwanto (Universitas Mataram, 2023)
Fertilizer is an important element in supporting the smooth productivity in farming activities. Fertilizer as a source of nutrients functions to nourish plants and improve soil quality so that it can affect plant growth and development. Therefore, the availability of meeting the needs of fertilizers in the agricultural sector needs to be re-optimized to increase production. This research uses a qualitative type with a case study approach that aims to analyze the survival strategy of the Sri Dadi Sugar Cane Farmers Group in Gondang Village, Karangrejo District as a result of the reform of the subsidized fertilizer distribution policy. The sampling technique was carried out by means of purposive sampling technique. Sources of data in this study were obtained from primary data through observation, in-depth interviews, documentation and secondary data. Analysis using interactive and theoretical models using James S. Coleman's Rational Choice Theory. The results showed that the survival strategy used by the Sri Dadi Sugar Cane Farmers Group included three aspects, namely (1) An active strategy was carried out by increasing knowledge and experience in sugarcane care, optimizing water and capital resources from the sale of sugar cane, and utilizing one's potential by looking for side jobs, and opening a personal business to meet the needs of family life. (2) The passive strategy aims to save operational costs by using liquid organic fertilizer. (3) Network strategy, namely establishing relationships with fellow sugarcane farmers and between farmer groups, village government, sugar cane traders, liquid organic fertilizer agents, and farm shops.